Exploration of Competency-Based Performance Management Practices in Driving Employee Career Development: A Case Study in the Financial Services Company - Fatimah Malini Lubis; Sami'un; Basyirah; Wenny Desty Febrian; I Ketut Kusuma Wijaya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This article explores Competency-Based Performance Management Practices (CBPMP) within the context of driving employee career development, focusing on a case study in a financial services company. The literature review delves into the foundational principles of CBPMP, emphasizing its role in aligning employee skills with organizational goals and fostering continuous improvement. Key themes include the identification of core competencies, performance appraisal methods, and the integration of career development pathways. The case study offers insights into how CBPMP strategies are implemented and their impact on employee motivation, skill enhancement, and career progression. Findings underscore the significance of strategic alignment between performance management and career development initiatives for achieving organizational success and employee satisfaction. The article contributes to the existing body of knowledge by highlighting best practices, challenges, and opportunities in leveraging CBPMP to enhance employee performance and career growth in the financial services sector.